The Pain in Alzheimer’s Disease – Diagnosis and Treatment - reports human trial data - Prucnal, Gabriela; Ryba, Karolina; Bukała, Martyna; Pudło, Kornelia; Zacher, Klaudia; Rakoczy, Anna; Walkiewicz, Patrycja; Frydrych, Jowita; Znamirowska, Katarzyna; Ochyra, Karolina (Quality in Sport, 2025)
Dementia diseases, led by Alzheimer’s disease (AD), are among the most common and serious conditions affecting the elderly. The number of people suffering from Alzheimer’s disease is increasing every year. Among these individuals, a significant portion experiences chronic pain, the diagnosis of which poses a major challenge due to communication difficulties with the patients suffering from Alzheimer’s disease. The objective of this publication is to provide an overview of the available methods for diagnosing and treating pain in patients with Alzheimer’s disease. The article presents the studies that utilized neuroimaging diagnostics and scales used to assess the severity and impact of pain on daily functioning, as well as the medications used. Neuroimaging studies indicate that while pain pathways are preserved in the early stages of Alzheimer’s disease, the response to pain stimuli diminishes in more advanced stages, potentially necessitating higher doses of analgesics in many AD patients. Effective treatment of chronic pain is crucial for improving the quality of life of patients, yet its diagnosis still presents many challenges due to communication difficulties with these individuals, the lack of precise scales, assessment methods, and the small number of individuals included in the studies.